The influence of rice bran oil blended and intake air temperature on combustion behaviours and knocking of single cylinder four stroke direct injection compression ignition engine - Norhafana, Mohamed (2024)
Energy is increasingly used around the globe daily for transportation purposes whether in air, land or sea. Most of the energy used in the transportation sector is extracted from the combustion processes in engines. Achieving complete combustion in an engine is essential for maximizing engine performance, fuel efficiency, and minimizing exhaust gas emissions. The properties of fuel in one of the several factors contribute to ensuring that the fuel-air mixture burns completely during the combustion process. When combustion is incomplete, some fuel molecules fail to burn completely, leading to the emission of various pollutants in the exhaust gases. Carbon dioxide, which is emitted mostly from the combustion of fossil fuels, is the most important gas that contributes to climate change. The urgency of creating alternative liquid-fuel energy sources has been highlighted by the twin crises of fossil fuel depletion and environmental degradation that have emerged in recent decades. As a result, there is a critical need to identify a renewable, clean, dependable, and cost-effective alternative energy source. Therefore, a thorough study of the influence of rice bran oil blended and intake air temperature is vital to fully understand the combustion process of direct injection compression ignition engine. The study starts with the examination of the physicochemical properties of rice bran oil blended in different percentages volume basis. Then, the study continues with the analysis of the effect of rice bran oil and intake air temperature on engine performance, combustion behaviors and knocking intensity of single-cylinder fourstroke direct injection compression ignition engine. The study focuses on the rice bran oil properties including density, kinematic viscosity, calorific value and cetane number according to American Society for Testing and Materials. Then, the investigation of the effect of fuel and intake air temperature is vital for the study of compression ignition engine operating with rice bran oil. The analysis includes the engine performance characteristics (brake power, brake specific fuel consumption, brake thermal efficiency, carbon monoxide, carbon dioxide, hydrocarbon and oxide of nitrogen), combustion behaviors (exhaust gas temperature, in-cylinder pressure, rate of heat release and rate of pressure rise) and lastly, knocking intensity. The experiment was performed using a KIPOR 170 FS single-cylinder, four-stroke, air-cooled, compression ignition engine. There are five fuel types involved in this study which are RBO00, RBO25, RBO50, RBO75, RBO100 with different operating conditions (engine speed, engine load, intake air temperature). The experimental results show that in general, the engine operating with rice bran oil and 45 °C intake air temperature produces higher brake thermal efficiency and higher brake specific fuel consumption (but still in optimal range 200 – 400 gkW/h) due to low energy content of rice bran oil as compared to pure diesel. The oxide of nitrogen emissions is slightly higher, but lower carbon monoxide and hydrocarbon are produced. The in-cylinder pressure and rate of heat release are slightly higher than pure diesel due to high cetane number and oxygen content then led to rapid premixing process and a reduce ignition delay for absolute combustion. Lastly, the observed knocking intensity was determined to be below the established threshold when the equivalency ratio was systematically varied within the range of 0.1 to 0.55. The experimental findings align with the literature review. In a nutshell, rice bran oil has been identified as a promising candidate as an alternative fuel due to its extensive resource availability and good performance qualities, and future work is recommended to improve the dynamics of compression ignition engine combustion.